Impact of STIMUlant and osmotic LAXatives (STIMULAX trial) on gastrointestinal recovery after colorectal surgery: randomized clinical trial. Issue 7 (3rd June 2021) - Dudi-Venkata, N N; Kroon, H M; Bedrikovetski, S; Lewis, M; Lawrence, M J; Hunter, R A; Moore, J W; Thomas, M L; Sammour, T
Abstract: Background: Recovery of gastrointestinal (GI) function is often delayed after colorectal surgery. Enhanced recovery protocols (ERPs) recommend routine laxative use, but evidence of benefit is unclear. This study aimed to investigate whether the addition of multimodal laxatives to an ERP improves return of GI function in patients undergoing colorectal surgery. Methods: This was a single-centre, parallel, open-label RCT. All adult patients undergoing elective colorectal resection or having stoma formation or reversal at the Royal Adelaide Hospital between August 2018 and May 2020 were recruited into the study. The STIMULAX group received oral Coloxyl ® with senna and macrogol, with a sodium phosphate enema in addition for right-sided operations. The control group received standard ERP postoperative care. The primary outcome was GI-2, a validated composite measure defined as the interval from surgery until first passage of stool and tolerance of solid intake for 24 h in the absence of vomiting. Secondary outcomes were the incidence of prolonged postoperative ileus (POI), duration of hospital stay, and postoperative complications. The analysis was performed on an intention-to-treat basis. Results: Of a total of 170 participants, 85 were randomized to each group. Median GI-2 was 1 day shorter in the STIMULAX compared with the control group (median 2  (i.q.r. 1.5–4) versus 3 (2–5.5) days; 95 per cent c.i. –1 to 0 days; P  = 0.029). The incidence of prolonged POI was lower in the STIMULAX group (22 versus 38 per cent; relative risk reduction 42 per cent; P  = 0.030). There was no difference in duration of hospital day or 30-day postoperative complications (including anastomotic leak) between the STIMULAX and control groups. Conclusion: Routine postoperative use of multimodal laxatives after elective colorectal surgery results in earlier recovery of gastrointestinal function and reduces the incidence of prolonged POI. Registration number: ACTRN12618001261202 (www.anzctr.org.au ) Abstract : Enhanced recovery protocols recommend routine laxative use for recovery of gastrointestinal function after colorectal surgery, but evidence for benefit is unclear. In this randomized controlled trial of 170 patients, return of gastrointestinal function after surgery was improved in patients receiving laxatives versus those in the non-laxatives group.